Facile Coating of Graphene Interlayer onto Li2S as a High Electrochemical Performance Cathode for Lithium Sulfur Battery - Van Chinh Hoang; VanDung Do; Nah, In Wook; Lee, Chongmok; Cho, Won Il; Oh, In Hwan (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Li2S with theoretical capacity of 1166 mAh g (1) has been considered as a promising candidate for Li-S cathode as it could be paired with safer Li-free electrodes to resolve safety issues. However, the success is hindered by the nature of Li2S and corresponding reduction species, including low conductivity and the shuttling phenomenon. Herein, we simply coat graphene films directly onto the Li2S cathode, which can suppress polysulfides dissolution effectively. The electrochemical performance of the cathode depending on graphene interlayer thickness (0, 20, 45, 54, 77 and 88 mu m) has been investigated. Li2S cathode with the 45 pm thick interlayer exhibits initial discharge capacity of 1029.21 mAh g (1) and 779.74 mAh g (1) at 0.05C and 0.1C, respectively, and capacity retention of above 60% with coulombic efficiency of around 90% over 300 cycles at high C rates. The results are discussed in terms of the graphene film thickness and the conductivity of the film as well as Li ion diffusivity. (C) 2016 Published by Elsevier Ltd.
Keywords: COMPOSITE CATHODES; CARBON; ION; NANOFIBERS; PAPER